Konsep dan Perkembangan Pemikiran Tentang Tanggung Jawab Sosial Perusahaan - Erman Rajagukguk (Fakultas Hukum Universitas Islam Indonesia, 2008)
The legal framework pertinent to Indonesian companies has assigned the companies to accomplish what so called by Corporate Social Responsibility (CSR). While in its wider concept CSR encompasses human rights, labor, consumers protection and environment, in its simpler concept, it is translated as the welfare development of the concerned surrounding community.